1984
DOI: 10.17660/actahortic.1984.161.8
|View full text |Cite
|
Sign up to set email alerts
|

Pear Breeding and Selection for Fire Blight Resistance

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…It has been proven that the selection of pear cultivars resistant to fire blight using phenotypic screening of breeding progeny is possible (Aldwinckle and van der Zwet 1979, Thibault and Paulin 1984, Hunter and Slingerland 2008). However, selection based entirely on phenotypic results is expensive, labour‐intensive and time‐consuming, because several replicates are necessary to estimate the level of fire blight resistance of genotypes and quarantine facilities are required in many countries (Khan et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been proven that the selection of pear cultivars resistant to fire blight using phenotypic screening of breeding progeny is possible (Aldwinckle and van der Zwet 1979, Thibault and Paulin 1984, Hunter and Slingerland 2008). However, selection based entirely on phenotypic results is expensive, labour‐intensive and time‐consuming, because several replicates are necessary to estimate the level of fire blight resistance of genotypes and quarantine facilities are required in many countries (Khan et al.…”
Section: Discussionmentioning
confidence: 99%
“…1968, Van der Zwet et al. 1974, Quamme and Bonn 1981, Thibault and Paulin 1984, Quamme et al. 1990).…”
unclassified
“…In this case, the MS3 fragment at 181 m/z was found to be a significant ion, which is known to be a characteristic RDA fragment for flavonoids that are methoxylated on the A ring, which is also the case with patuletin [73]. (20), 316 (11), 477(100), 478 (17), 479 (5), 519 (20), 593 (9) 283 (10), 299 (34), 314 (18), 315 (49), 316 (6), 342 (7), 462(100)…”
Section: Identification Of Pear Nectar Polyphenolicsmentioning
confidence: 78%
“…It is the major factor that significantly limits the cultivation of the European pear, especially in regions where springtime weather is warm and wet during blossoming [9]. Resistance to fire blight in the European pear was found by Hevesi et al [10] in Hungarian Sikulai and Szemes Alma cultivars, and in P. pyrifolia, P. ussuriensis or in hybrids between P. communis and these species [11].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies in the past indicated that fire blight resistance is polygenic, quantitative and controlled by multiple genes with additive effects (Quamme & Bonn, 1981; Quamme et al., 1990; Thibault & Paulin, 1984; Van Der Zwet et al., 1974). However, there is evidence that resistance is controlled by a major gene (Bell, 2019).…”
Section: Introductionmentioning
confidence: 99%